(تنمية مهارة القراءة لدي الطلاب باستخدام لعبة " فلاش" (بحث تطويري في قسم تعليم اللغة العربية بالجامعة الاسلامية الفلاح السنية - Abdillah, Mochammad Khakam Majid (Al-Fusha : Arabic Language Education Journal, 2018)
This research is based on the students weakness ability in reading Arabic text. It could be happened because learning activities and tecniques tend to be tedious. So they need a new way to make lesson not make them bored. The purpose of this study is to describe the implementation of learning and increasing the ability of students to understand the Arabic texts through the use of the language game “Flash” at IAI Al-Falah As-Sunniyyah Kencong Jember. The researcher use R&D approach to apply this study. The results of this study are: First, the students can play the game “Flash” in developing their reading skill ability. Second, the teacher can reach the learning goal easily. Third, the ????lash game can develop the students reading skills effectively.